Traslados: la distancia y el olvido de los otros (Tema Central) - Altamirano Espinosa, Luis Hernán (2024)
I plan to expose the difficult legal situation of deprivation of liberty and transfers to different deprivation of liberty centers. To do this, it is necessary to verify the theories of punishment that our legal system intends to follow, which will allow us to know the reasons for the regulations issued regarding penitentiary guarantees. Likewise, know the regulatory status of transfers and their immediate relationship with habeas corpus. The path that is intended to be followed between the supposed denaturalization of jurisdictional guarantees and the absence of judicial control. Likewise, raise the relationship that exists on transfers and other prison conflicts such as overcrowding, violence and lack of prison staff and that has an impact on several constitutional rights such as family unity, the right to defense, among others. Finally, possible solutions are sought to the problems caused by the transfers of people deprived of liberty, especially on the contradiction between article 668.2 of the COIP that prevents transfers through a jurisdictional guarantee and the sentence of the Court Constitutional n.º365-18-JH/21 and accumulated (Personal integrity of persons deprived of liberty) that enables the possibility of carrying it out in cases of impact on the right to personal integrity.